Age-Related Changes in Intraocular Pressure: Japan Ningen Dock Study. Issue 12 (24th December 2022) - Terauchi, Ryo; Wada, Takashi; Fukai, Kota; Tatemichi, Masayuki; Ogawa, Shumpei; Noro, Takahiko; Ito, Kyoko; Kato, Tomohiro; Kato, Kiminori; Nakano, Tadashi
Abstract : Précis: The analysis of intraocular pressure by age using a mega database showed a consistent age-related intraocular pressure decrease. Purpose: To clarify the association between age and intraocular pressure (IOP), the IOP value by age was assessed using a large IOP database. Materials and Methods: This cross-sectional study was conducted among 103 health checkup institutions registered to the Japan Society of Ningen Dock, and included participants who underwent annual health checkups between April 2014 and March 2015. The inclusion criteria were as follows: complete data for IOP in eyes, body mass index, waist circumference, blood pressure, hemoglobin A1c, and a self-administered health questionnaire. A total of 655, 818 participants were enrolled. The mean age was 51.5±10.5 years (range, 20–96 y), and 40.1% were women. IOP was measured using a noncontact tonometer. Multiple linear regression analysis was conducted to explore factors associated with IOP, including age, and analyses stratified by age group: <40, 40–69, and ≥70 years. Results: A consistent negative association between IOP and age [β=−0.353 (95% confidence interval: −0.360–−0.346)] was observed. In the age groups of <40 and ≥70 years, the age-related IOP decline was more pronounced [β=−0.502 (95% CI: −0.566 to –0.439); β=−0.674 (95% CI: −0.753 to –0.595)], with it being 14.21±2.95 and 11.18±2.52 mm Hg in the 20–24 and 90–96 year age groups, respectively. The middle-aged (aged 40–69 y) population showed gradual decline [β=−0.313 (95% CI: −0.323 to –0.303)]. Conclusion: Age was strongly and negatively associated with IOP. The magnitude of IOP decline across lifespans was ∼3 mmHg. Age-related decreases in IOP were nonlinear and phasic.